Harmonic Compensation using STATCOM for SEIG Feeding Single-Phase Load Connected between Different Phases - Satyanarayan Gorantla; Goli Ravi Kumar (Institute of Advanced Engineering and Science, 2017)
The paper presents the analysis of harmonic distortion when non-linear load is connected in different phases of power system with STATCOM for singly excited induction generator system with wind turbine as prime mover. Now-a-days due to the drastically increased in use of non linear loads causes many power quality problems in power system network. Those problems are classified as reactive power problems, harmonics, voltage sags and swells. Out of these problems harmonic problems are major concern. Custom power devices proposed for mitigation of power quality in network. For compensation of harmonic, static compensator (STATCOM) is used. The paper presents the compensation of harmonic power quality issues using STATCOM for the system with singly-excited induction generator feeding non-linear load connected in different phases. STATCOM is controlled using synchronous reference frame theory to produce pulses to switches of STATCOM sensing the input parameters. Proposed concept was developed using MATLAB/SIMULINK software and results are presented for non-linear load connected in different phases of the power system. THD analysis was shown for source current and load current for different cases.